An Overview of the Outcomes of Learning English with or without Materials in DRC: The Case of English and Business Computer Science. - Manyole Odida, Banyongi (International Journal of Scientific Research and Management (IJSRM), 2022)
This article has given an overview of the outcomes of learning English with or without materials. It has proved through the findings that the material-bound learners have a greater advantage than the material-free ones. The material-bound outcomes or performance far outweigh the material-free ones, which is why the material qualifies to have a positive effect and influence on the process of English language learning.